Complying with the smoking ban by students before and after introducing legislative intervention - Adam Rzeźnicki (International Journal of Occupational Medicine and Environmental Health, 2015)
Objectives: More and more countries introduce a total ban on smoking tobacco in public places. The aim of this work was to evaluate the effectiveness of “The Act of 8 April 2010 on amendment of the act on protection of health against the consequences of consumption of tobacco and tobacco products and act on National Sanitary Inspectorate” and assess the frequency of complying with the smoking bans by the students of the Medical University of Lodz, Poland. Material and Methods: Between 2007–2011, at the Social Medicine Institute of the Medical University of Lodz, a study using random survey was carried out involving students who were starting their studies at the Health Department of the Medical University of Lodz. The analysis of the collected material showed that 1038 people reported being smokers at the time of the study. Among that group, 530 students were included in the study prior to, and 508 after the introduction of the amendment. In order to verify their compliance with the smoking ban, the respondents were asked whether they smoked only in designated areas or wherever they wanted to. Results: The ratio of people claiming they smoked anywhere they wanted to, disregarding the smoking ban, was 60% (N = 318) and after the amendment had been introduced, this ratio was 62.2% (N = 316), it increased by 2.2 percentage points. The observed difference was statistically irrelevant (Chi2 = 0.530, p > 0.05). Conclusions: The Act ”On amendment of the act on protection of health against the consequences of consumption of tobacco and tobacco products and Act on National Sanitary Inspectorate” in Poland did not result in the expected changes in the frequency of complying with the smoking ban by the 1st year students.